POTENSI LIMBAH KERAK TUNGKU PEMBAKARAN GENTENG SEBAGAI FILLER ALTERNATIF PADA CAMPURAN ASPAL BETON - Satria Pradana; Hartatik, Nurani; Ismoyo, Alif Setyo; Punarta, I Gede Agus (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
The utilization of industrial waste as a construction material is a strategic step in supporting sustainable development. In this context,the study was conducted to evaluate the characteristics of tile kiln crust waste as a substitute for filler in asphalt concrete mixture. Thewaste was obtained from tile production in Kencong Village, Kediri Regency, East Java, then processed into fine powder before beingused in the mixture. This study was conducted at the National Road Implementation Center Laboratory, with a series of tests includingsieve analysis, determination of specific gravity, and X-Ray Fluorescense (XRF) test. Based on the results of the sieve analysis test, itshowed that 77.63% of tile kiln crust powder filler particles could pass through the No. 200 sieve, while the specific gravity value ofthe material was 2.713. Meanwhile, the results of the XRF analysis indicated that the content of CaO (12.3%), SiO2 (36.7), and AI2O3(12%) were the main elements, with characteristics resembling limestone filler. Based on the test results, it shows that the waste of theroof tile kiln crust has met the criteria as a filler in the asphalt concrete mixture according to the Bina Marga 2018 specifications(Revision 2). The use of this waste not only contributes to increasing the stability of the asphalt mixture, but also becomes anenvironmentally friendly waste management solution. Therefore, tile kiln slag waste has significant potential to be applied as a fillersubstitute in road paveent construction.Keyword: Tile Waste, Filler, Marshall, Asphalt Concrete